Practical Node.js building real-world scalable web apps - Mardan, Azat (Apress, 2014)
If you already know the basics of Node.js, now is the time to discover how to bring it to production level by leveraging its vast ecosystem of packages. As a web developer, you'll work with a varied collection of standards and frameworks - Practical Node.js shows you how all those pieces fit together. Practical Node.js takes you from installing all the necessary modules to writing full-stack web applications by harnessing the power of the Express.js and Hapi frameworks, the MongoDB database with Mongoskin and Mongoose, Jade and Handlebars template engines, Stylus and LESS CSS languages, OAuth and Everyauth libraries, and the Socket. IO and Derby libraries, and everything in between. The book also covers how to deploy to Heroku and AWS, daemonize apps, and write REST APIs. You'll build full-stack real-world Node.js apps from scratch, and also discover how to write your own Node.js modules and publish them on NPM. What you'll learn: Manipulate data from the mongo console; Use the Mongoskin and Mongoose MongoDB libraries; Build REST API servers with Express and Hapi; Deploy apps to Heroku and AWS; Test services with Mocha, Expect and TravisCI; Utilize sessions for authentication; Implement a third-party OAuth strategy with Everyauth; Apply Redis, domains, WebSockets, and clusters; Write your own Node.js module, and publish it on NPM. --
Includes index. - Includes bibliographical references and index. - Online resource; title from PDF title page (SpringerLink, viewed July 28, 2014)
Keywords: Node.js; Web applications; Applications Web; COMPUTERS; General